Komunikasi Politik Non-Elektoral dalam Relasi Digital Pengguna Bumble: Micro Politics in Platform Society - Jamalullail (Jurnal Spektrum Komunikasi, 2026)
In the context of digital intimate relationships, this research looks at user interactions on the dating app Bumble as a platform for non-electoral politics. This research argues that power functions via everyday communicative practices made possible by digital platforms in addition to electoral-focused strategies in political communication studies. Instead of being purely private spaces cut off from power dynamics in the context of platform culture, personal relationships are increasingly social arenas where visibility, recognition, and vulnerability are continuously contested. In addition to interface walkthroughs and an analysis of platform policy documents, the study uses an interpretive qualitative technique that includes in-depth interviews with active Bumble users in urban settings. Intimate digital connections may be analysed as social practices impacted by platform design and governance as well as subjective experiences thanks to this analytical method. The results show that in addition to controlling technical interaction, mechanisms like swiping, algorithmic matching, time-limited conversations, and the "women make the first move" feature represent a type of relational governance that leads to unequal vulnerability, visibility, and acknowledgement. Self-presentation, self-disclosure, and ghosting are examples of how users manage identity, risk, and emotion within complex power structures embedded in platform designs and interactional norms. The results imply that rather than via overt dominance, power is used in digital intimate relationships as micro-political arenas where speed, attentiveness, and behavioural norms are regulated. By including platform governance and politics-as-practice viewpoints into the study of modern digital connections, this paper theoretically expands political communication studies by validating individual communicative activities as a crucial site of political analysis.